The Length of N-Glycans of Recombinant H5N1 Hemagglutinin Influences the Oligomerization and Immunogenicity of Vaccine Antigen - Macioła, Agnieszka Katarzyna; Pietrzak, Maria Anna; Kosson, Piotr; Czarnocki-Cieciura, Mariusz; Śmietanka, Krzysztof; Minta, Zenon; Kopera, Edyta (Frontiers in Immunology, 2017)
Hemagglutinin glycoprotein (HA) is a principal influenza vaccine antigen. Recombinant-HA based vaccines become a potential alternative for traditional approach. Complexity and variation of HA N-glycosylation are considered as the important factors for the vaccine design. The number and location of glycan moieties in the HA molecule are also crucial. Therefore we decided to study the effect of N-glycosylation pattern on the H5 antigen structure and its ability to induce immunological response. We also decided to change neither the number nor position of the HA glycosylation sites but only the glycan length. Two variants of the H5 antigen with high mannose glycosylation (H5hm) and with low mannose glycosylation (H5Man5) were prepared utilizing different Pichia strains. Our structural studies demonstrated that only the highly glycosylated H5 antigen formed high molecular weight oligomers similar to viral particles. Further, the H5hm was much more immunogenic for mice than H5Man5. In summary, our results suggest that high mannose glycosylation of vaccine antigen is superior to the low glycosylation pattern. Our findings have strong implications for the recombinant HA-based influenza vaccine design.